KOMPETENSI GURU DI MASA PANDEMI COVID-19 - jajat sudrajat (Universitas Semarang, 2020)
This paper discusses the competence of teachers during the Pandemic COVID 19. Various policies and the implementation of health protocols were carried out to break the chain of distribution of Covid-19, impacting on teachers who are required to teach online. Using a qualitative approach, a descriptive analytical method, it was found that teacher competencies related to literacy and science and technology mastery competencies, class management skills competencies and communication and social competencies, were not optimal. Development of these competencies is needed so that it will minimize the problems that exist in online learning, so that the learning process can run better.